Ethno-Medicinal Study on Garlic for Women and Occupational Health Using Herbs that Mentioned in Al-Quran and Hadith - Nurulwahidah Fauzi; Khadher Ahmad; Monika Munirah Abd Razzak; Khalijah Awang; Mohd Asmadi Yakob; Rozana Othman; Mohd Farhan Md Sariffin; Muhd Widus Sempo (Medwell Journals, 2024)
Non-Indexed Publication